Management Practices against Angoumois grain moth, Sitotroga Cerealella (Olivier) in Stored Paddy in Nagaland, India - Jamir, I. T. Asangla; Alemla Ao, M.; Khound, J. N. (International Journal of Bio-resource and Stress Management, 2023)
Sitotroga cerealella (Olivier) is one of the most destructive insect-pests of Nagaland. Experiments on management practices during the year 1998-1999& 1999-2000 are stated below. Highest efficacy among 12 plant materials was shown by L. citrata seed powder @ 10g kg-1 throughout the period of study; lowest result was in A.indica oil cake @ 5 g kg-1 at 2 months, Z.oxyphyllum leaf powder@ 5 g kg-1 at 4 and 6 months of storage. Malathion @ 1.5 g kg-1 was the best treatment in all the months of storage. Ahning with Tsakvong indicated that the pest result out of 8 storage structures whereas gunny bag storage showed the highest infestation in all the months of storage. Best germination was presented in Ahning with Tsakvong. Analysis of correlation coefficient (r) of percent germination of seeds with infestation percentage of Sitotroga cerealella had indicated inverse relation infestation with germination percentage. Estimates on linear regression coefficient (b) for germination percentage of rice seeds with infestation percentage of Sitotroga cerealella was carried out in all the parameters.